(untitled) (Journal of Health, Population and Nutrition, 2013)
The study examined the influence of fish oil (FO) supplementation on serum 8-hydroxy-2-deoxyguanosine (8-OHdG) levels as indicated by DNA damage markers and total antioxidant capacity (TAC) among male cigarette smokers. This double-blind, placebo-controlled randomized study was conducted among healthy cigarette smokers (n=40) who were part of a larger prospective cohort study. Twenty smokers were randomly selected to receive FO for 3 months (1 g/day), and another 20 smokers received a placebo for 3 months; 8-OHdG and TAC levels were measured in blood samples before and after the intervention. Serum 8-OHdG significantly decreased (p=0.001) and TAC increased (p<0.001) after 3 months of treatment with FO. Between baseline and endline, the difference in 8-OHdG significantly correlated with the difference in TAC among smokers who received FO (r=-0.540, p=0.014). The study provides evidence that FO supplementation can modify decreased antioxidants and increased oxidative DNA damage in cigarette smokers. DOI: http://dx.doi.org/10.3329/jhpn.v31i3.16826 J HEALTH POPUL NUTR 2013 Sep; 31(3): 343-349